MEDIA INFORMASI BERBASIS AUGMENTED REALITY PADA KOMPLEKS MASJID AGUNG KERATON BUTON MENGGUNAKAN ALGORITMA FAST CORNER DETECTION - Nalis Hendrawan; Helson Hamid; Baidi Azzamani (Prodi Teknik Informatika Unidayan Baubau, 2022)
The Great Mosque of the Buton Palace was built in 1917 by Sultan Sakiudin Durul Alam and is a very important area and has historical value during the Buton Sultanate. This mosque is located within the Buton Palace Fortress area (Wolio Fort). The lack of knowledge about the area is caused by very little written information about the Buton Palace Grand Mosque Complex. The purpose of this research is to design and build an information media based on Augmented Reality so that it becomes informative media for the public. This Information Media uses Augmented Reality technology with the FAST Corner Detection Algorithm. From the research that has been done, Augmented Reality technology using the FAST Corner Detection Algorithm gets good results when used as an information medium and its application on Android devices. The results are proven through accuracy testing with a distance of 10cm - 100cm and an angle of 45o - 90o with an accuracy of 10cm-20cm which is not successful and 30cm-100cm is successful and there is a delay.